APLIKASI HIJAB SHAHABIYAT DI MASA TURUN PERINTAH MENUTUP AURAT (Studi Pemahaman Sosio-Historis Hadis Perilaku Wanita Masa Nabi) - Muhammad Arpah Nurhayat; Anggi Wahyu Ari (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
In the aspect of Islamic shari'a, it stipulates matters of daily application, including the manner of dress which is permissible in the Koran. Women get more attention in this matter, considering that their bodies contain beauty that must be covered so that it does not become a spectacle and slander for the opposite sex which is not their muhrim, it is then called aurat. The opinion of the majority of the Ulama is that male genitalia is from the navel to the knees while the female genitalia is the entire body except the face and palms. This article discusses how the application of the hijab in the days of the decree to close the aurat. hijab in the sense of closing the aurat is the command of Allah through his apostle but the boundary of the hijab is not agreed upon by the ulama. In the early days of sahabiyyat, covering their faces and heads, the implementation of the hijab by covering the entire body, including the head and face, was a response to the obedience of sahaiyyat against the command to use the hijab, not a shari'ah order from the Prophet. over time the trend of hijab appears to be inseparable from each other's understanding of the boundaries of women's genitals so that the veil, niqab, and khimar appear, all of which refer to the order to cover the genitals and are greatly affected by the boundaries of the aurat's understanding and fatwa of the ulema.